Designing visible-light optical coherence tomography towards clinics - Shu, Xiao (Quant Imaging Med Surg, 2019)
BACKGROUND: The capabilities of visible-light optical coherence tomography (vis-OCT) in noninvasive anatomical and functional retinal imaging have been demonstrated by multiple groups in both rodents and healthy human subjects. Translating laboratory prototypes to an integrated clinical-environment-friendly system is required to explore the full potential of vis-OCT in disease management. METHODS: We developed and optimized a portable vis-OCT system for human retinal imaging in clinical settings. We acquired raster- and circular-scan images from both healthy and diseased human eyes. RESULTS: The new vis-OCT provided high-quality retinal images of both subjects without any known eye diseases and patients with various retinal diseases, including retinal occlusive disease and diabetic retinopathy (DR) over a broad range of ages. CONCLUSIONS: A newly designed vis-OCT system is sufficiently optimized to be suited for routine patients’ examinations in clinics. Vis-OCT has the potential to add new anatomical and functional imaging capabilities to ophthalmic clinical care.